Human responses to simulated motorized noise in national parks - Weinzimmer, David, author; Newman, Peter, advisor; Manfredo, Michael, committee member; Bell, Paul, committee member (Colorado State University. Libraries, 2013)
This thesis investigated the effects of three sources of motorized noise on laboratory participants' evaluations of landscape scenes, self-reported affective states, and physiological responses in simulated national park settings. Seventy-seven laboratory participants completed landscape assessments along 8 aesthetic dimensions and reported affective states while listening to audio clips of natural sounds, propeller planes, motorcycles, and snowmobiles. Each participant experienced all scenes and sound conditions in a pseudo-randomized order. The change from the natural sound baseline for each motorized source of noise was calculated. Results indicated that all motorized sources of noise had detrimental impacts on landscape assessments and self-reported affective states, compared to natural sounds. Motorcycle noise was demonstrated to have the largest negative impact on landscape assessments. Physiological response was also affected by experimental noise in some of the conditions (with the strongest effect in the snowmobile condition), but a consistent pattern of results failed to emerge to suggest that negative impacts to human physiology could be reliably detected under the present methodology. In addition to confirming that noise from motorized recreation has significant social impacts on potential park visitors, this simulation suggests that the specific source of the noise is an important factor in observer evaluations. These results could help park managers prioritize their educational and regulatory strategies for minimizing adverse impacts by motorized vehicles on natural soundscapes. Important advances in soundscape research methodology are also presented.
Keywords: affect; motorized; noise; physiology; simulation; soundscapes